2005
DOI: 10.1016/j.jcrs.2005.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound thermal damage to rabbit corneas after simulated phacoemulsification

Abstract: Rabbit corneas showed a considerable tolerance to US damage up to 50 degrees C. Higher thermal doses produced severe histological damage, even though corneas showed a considerable plasticity due to their regenerative capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 12 publications
2
24
0
1
Order By: Relevance
“…In patients in whom the endothelial gaping and the endothelial misalignment were concurrently present, the corneal edema at the endothelial side of the incision was found to be more severe. The corneal swelling was largely caused by wound damage during surgery, including mechanical trauma induced by the insertion of surgical instruments and direct damage by the force of phacoemulsification or by transformed heat [21]. Mackool et al [22] reported that stretching and tearing of the wound may happen when surgical instruments are forced into the anterior chamber, especially when the incision tunnel is too tight.…”
Section: Discussionmentioning
confidence: 99%
“…In patients in whom the endothelial gaping and the endothelial misalignment were concurrently present, the corneal edema at the endothelial side of the incision was found to be more severe. The corneal swelling was largely caused by wound damage during surgery, including mechanical trauma induced by the insertion of surgical instruments and direct damage by the force of phacoemulsification or by transformed heat [21]. Mackool et al [22] reported that stretching and tearing of the wound may happen when surgical instruments are forced into the anterior chamber, especially when the incision tunnel is too tight.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits have been widely used as an experimental model for ophthalmic research (ATILLA et al, 2003;MENCUCCI et al, 2005;ARI et al, 2015). The goal of the present study was to evaluate the cell density and percentage of hexagonal cells because these are the most reliable parameters for evaluating the integrity of the corneal endothelium (ABIB & BARRETO, 2001;PIGATTO et al, 2006;NAGATSUYU et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that rabbit corneal endothelium repairs by cell division and Brambatti et al migration (MORITA, 1995). Rabbits have been widely employed in the evaluation of the effects of surgical procedures and drugs on the corneal endothelium (ATILLA et al, 2003;MENCUCCI et al, 2005;ARI et al, 2015). However, there are few published references regarding endothelial density in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to light from the operating microscope might also be associated with postoperative dry eye (Cho and Kim, 2009). Furthermore, the use of ultrasound in cataract surgery may damage corneal structures such as the epithelium, stroma, keratocyte, endothelium, and nerve plexuses (Mencucci et al, 2005). Ocular surface complications are much rarer following small incision phacoemulsification.…”
Section: Dry Eye In Cataract Patientsmentioning
confidence: 99%